To be a citizen in the twenty-first century - "Hareven, Alouph" (New Delhi, 1996)
The past 10 years have seen the greatest expansion of information since the dawn of civilization. According to Google$1 (Bs chairman Eric Schmidt, human beings create every two days as much information as we did since the birth of humanity up until 2003. Today, two-thirds of human beings are connected to the Internet and there are more mobile phones than people on the planet. At the same time, computing power doubles every 18 months and in the next decade we will see a machine with the processing power of a human brain.s
Keywords: Citizenship